Dyskinesia‐inducing lead contacts optimize outcome of subthalamic stimulation in Parkinson's disease. Issue 11 (30th September 2019) - Bouthour, Walid; Béreau, Matthieu; Kibleur, Astrid; Zacharia, André; Tomkova Chaoui, Emilie; Fleury, Vanessa; Benis, Damien; Momjian, Shahan; Bally, Julien; Lüscher, Christian; Krack, Paul; Burkhard, Pierre R.
Abstract: Background: Acute dyskinesias elicited by STN‐DBS, here referred to as stimulation‐induced dyskinesias, predict optimal clinical outcome in PD. However, it remains elusive whether stimulation‐induced dyskinesias can guide DBS programming. Objectives: Here, we characterized stimulation‐induced dyskinesias clinically and anatomically. We then tested whether dyskinesia‐inducing contacts could be effectively programmed using independent current source technology. Methods: We characterized stimulation‐induced dyskinesias with directional and ring stimulation retrospectively in 20 patients. We then localized dyskinesia‐inducing contacts by imaging coregistration and eventually programmed those contacts. Results: We elicited dyskinesias in half of our patients. Dyskinesia‐inducing contacts were mainly directional and were all located ventrally within the dorsolateral motor STN. When these dyskinesia‐inducing contacts were programmed using independent current source technology, dyskinesia disappeared and robust antibradykinetic effects were obtained. Conclusion: We confirm that stimulation‐induced dyskinesias are helpful clinical observations, which may guide programming of directional STN‐DBS in PD. © 2019 International Parkinson and Movement Disorder Society